Biochar, microbes, and biochar-microbe synergistic treatment of chlorinated hydrocarbons in groundwater: a review - Niu, Shixin; Li, Changsuo; Gao, Shuai; Tian, Jingya; Zhang, Chao; Li, Lixia; Huang, Yao; Lyu, Honghong (Frontiers in Microbiology, 2024)
Dehalogenating bacteria are still deficient when targeted to deal with chlorinated hydrocarbons (CHCs) contamination: e.g. slow metabolic rates, limited substrate range, formation of toxic intermediates. To enhance its dechlorination capacity, biochar and its composites with appropriate surface activity and biocompatibility are selected for coupled dechlorination. Because of its special surface physical and chemical properties, it promotes biofilm formation by dehalogenating bacteria on its surface and improves the living environment for dehalogenating bacteria. Next, biochar and its composites provide active sites for the removal of CHCs through adsorption, activation and catalysis. These sites can be specific metal centers, functional groups or structural defects. Under microbial mediation, these sites can undergo activation and catalytic cycles, thereby increasing dechlorination efficiency. However, there is a lack of systematic understanding of the mechanisms of dechlorination in biogenic and abiogenic systems based on biochar. Therefore, this article comprehensively summarises the recent research progress of biochar and its composites as a "Taiwan balm" for the degradation of CHCs in terms of adsorption, catalysis, improvement of microbial community structure and promotion of degradation and metabolism of CHCs. The removal efficiency, influencing factors and reaction mechanism of the degraded CHCs were also discussed. The following conclusions were drawn, in the pure biochar system, the CHCs are fixed to its surface by adsorption through chemical bonds on its surface; the biochar composite material relies on persistent free radicals and electron shuttle mechanisms to react with CHCs, disrupting their molecular structure and reducing them; biochar-coupled microorganisms reduce CHCs primarily by forming an "electron shuttle bridge" between biological and non-biological organisms. Finally, the experimental directions to be carried out in the future are suggested to explore the optimal solution to improve the treatment efficiency of CHCs in water.